COMBINED MANTLE PLUME-ISLAND ARC MODEL FOR THE FORMATION OF THE 2.9 GA SUMOZERO-KENOZERO GREENSTONE BELT, SE BALTIC SHIELD: ISOTOPE AND TRACE ELEMENT CONSTRAINTS - Puchtel I.S.; Hofmann A.W.; Amelin Yu.V.; Garbe-Schönberg C.D.; Samsonov A.V.; Shchipansky A.A. (My University, 1999)
The Sumozero-Kenozero greenstone belt in the SE Baltic Shield is ∼400 km long and up to 50 km wide and includes two main units with a total thickness of ∼5 km. The lower unit consists of oceanic plateau-type submarine mafic-ultramafic lavas. The upper unit is made up of island arc-type volcanic BADR (basalt-andesite-dacite-rhyolite)-series rocks and adakite-series subvolcanic rhyolites. Both units are separated by major thrust zones from the 3.2 Ga TTG-gneisses of the Vodla Block microcontinent.